2021
DOI: 10.1080/19490976.2021.1988836
|View full text |Cite
|
Sign up to set email alerts
|

Fungal lysozyme leverages the gut microbiota to curb DSS-induced colitis

Abstract: Colitis is characterized by colonic inflammation and impaired gut health. Both features aggravate obesity and insulin resistance. Host defense peptides (HDPs) are key regulators of gut homeostasis and generally malfunctioning in above-mentioned conditions. We aimed here to improve bowel function in diet-induced obesity and chemically induced colitis through daily oral administration of lysozyme, a well-characterized HDP, derived from Acremonium alcalophilum . C57BL6/J mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 80 publications
0
24
1
Order By: Relevance
“…However, microbiota-deficient mice, e.g., germ free mice, have altered immunity and ethanol metabolism which confound the protective effects of hBD-2 (Chen et al, 2015). A previous report regarding the use of another AMP, fungal lysozyme, showed that in an experimental colitis model the presence of gut microbiota was required for the therapeutic effects of the treatment (Larsen et al, 2021), suggesting that the effects of hBD-2 may similarly be microbiotadependent.…”
Section: Discussionmentioning
confidence: 99%
“…However, microbiota-deficient mice, e.g., germ free mice, have altered immunity and ethanol metabolism which confound the protective effects of hBD-2 (Chen et al, 2015). A previous report regarding the use of another AMP, fungal lysozyme, showed that in an experimental colitis model the presence of gut microbiota was required for the therapeutic effects of the treatment (Larsen et al, 2021), suggesting that the effects of hBD-2 may similarly be microbiotadependent.…”
Section: Discussionmentioning
confidence: 99%
“…Olu et al confirmed that oral administration of Akkermansia muciniphila strain BAA-835 considerably ameliorated colitis by modulating intestinal microecology [ 45 ]. Larsen et al reported that lysozyme leveraged gut microbiota to inhibit DSS-induced colitis [ 46 ]. These findings indicate that restoring gut microbiota is conducive to alleviating colitis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, both genetic and diet-induced Paneth cell dysfunctions promote increased inflammatory reactions towards mutualistic bacteria, enhancing bacterial translocation and mucosal inflammation [ 101 , 109 , 112 , 113 ]. Further supporting the relevance of HDPs in maintaining and even re-establishing homeostasis, oral administration of fungal lysozyme enhances the bacterial lysis zone near the epithelium in HFD-fed mice, thereby shielding the mucosal immune system from microbial exposure [ 114 ]. Intriguingly, microbial lysis is not exclusively beneficial and the phenotypic trait of mammalian lysozyme activity is vastly influenced by the inflammatory tone and anatomical compartment.…”
Section: Shaping the Gut Microbiotamentioning
confidence: 99%
“…Fungal lysozyme appears capable of leveraging the gut microbiota to dose-dependently alleviate experimental colitis. Diminished colitis was followed by increased colonic R. gnavus abundances in two genotypes, both sexes, and across three geographically and inter-continent separated facilities, pointing towards a markedly different microbiota imprinting ability of GH25 family lysozymes compared to GH22 family lysozymes [ 114 ].…”
Section: Shaping the Gut Microbiotamentioning
confidence: 99%